Study of the basic chemical composition and some biological compounds in carob seeds - يوسف حسين; رامز محمد; ياسر قرحيلي (Latakia University Journal -Biological Sciences Series, 2024)
Ceratonia siliqua, commonly known as carob, is considered one of the important fruit-bearing trees with distinctive characteristics renowned in Asia and Africa. Carob fruits consist of pulp and seeds that contain vital components. Carob is widely used in various food industries as an antioxidant, thickener, stabilizer, emulsifier, and also as a cocoa substitute, it is used in the bakery industry. In this study, the chemical components of Syrian carob seeds, collected from carob trees at Tishreen University, were examined. The moisture content in the seeds was estimated and found to be 0.06 ± 8.04%. The remaining components were determined based on 100 grams of dry weight. The protein content was measured to be 0.05 ± 29.98%, the lipid content was 0.06 ± 3.95%, the fiber content was 0.1 ± 12.77%, the ash content was 0.02 ± 3.81%, the acidity based on oleic acid was 0.07 ± 5.01%, the total sugar content was 0.01 ± 3.65%, and Polyphenols were estimated on the basis of mg gallic acid per gram of dry seeds and their value was 0.01 ± 22.37%. As for the antioxidant capacity, it was measured as 0.32 ± 71.36 using the Di Phenyl Picryl Hdrazyl (DPPH) method and 1.15 ± 699.33 using the Ferric Reducing Antioxidant Power (FRAP) method.